Improving Discipline Analysis of High School Students with Guidance and Counseling approaches - Lita Gustiana; Daharnis Daharnis; Marjohan Marjohan (Universitas Negeri Padang, 2020)
Discipline is defined as the compliance with existing rules or regulations with pleasure and self-awareness. It has a huge influence on learning, personal interest, social life and career of students. Therefore, the purpose of this study is to describe the disciplinary problems of students at SMAN 2 Padang and ways to improve it using the right counseling approach. Data was analyzed using the quantitative and descriptive methods with a reliability scale of 0.909. The research findings shows the discipline of students in SMAN 2 Padang is in the sufficient category with a percentage of 79.27%in accordancewith established rules. Therefore the Rational Emotional Behavior Therapy group format approach is developed to enhance the problem of proper student discipline.